Enhancing Job Satisfaction Among Public Health Civil Servants: The Mediating Role of Transformational Leadership - Bachsyuan Zami Hasan; Rahmat Sabuhari; Nurlaela; Abdul Wahab Hasyim (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study examines the effect of work motivation on job satisfaction among State Civil Apparatus (ASN) employees in public health service units of Central Halmahera Regency and investigates the mediating role of transformational leadership. A quantitative survey approach was employed, involving 418 ASN working in public health service units. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that work motivation has a positive and significant effect on job satisfaction and transformational leadership. Transformational leadership also positively and significantly influences job satisfaction. Furthermore, transformational leadership partially mediates the relationship between work motivation and job satisfaction. These results suggest that employee job satisfaction is shaped not only by individual motivation but also by leadership practices that inspire, support, and engage employees. The study highlights the importance of strengthening work motivation and promoting transformational leadership to improve employee satisfaction and support the effectiveness of public health service delivery.